The role of street art in state-led gentrification : case study on Mural Istanbul - Türken, Hazal (2019)
The main purpose of the research is to examine the role of public sponsored street art implications in gentrification. The research data was conducted through participatory observation and in-depth interviews in the on-going revitalization project area; the Yeldeğirmeni neighbourhood in Istanbul, Turkey. The analysis of the data presented that there is an on-going and avoided gentrification process in the neighbourhood. Moreover, it was understood that the Mural Istanbul Street Art Festival is aimed by municipality to aestheticize the process as well as trigger gentrification in the streets. Outcome of the study represents that the festival serves as a tool to form the culture of the district without making any visibly destructive implementation in the long-term. Apart from that, the interviews mirrored the motivation of artists and their position regarding the gentrification process. Whereas some preferred to remain silent, most artists stated that they acknowledge the instrumentalization of street art to trigger gentrification. Additionally, it was found that the action of transforming the city is understood as claiming the right to the city by both the artists and the municipality.